(3LhGgQ Gdcde GdSfjI hHOGFY GdMce GdfHhjIs - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf aj GdCdaGX GdfHhjI GdTQYjI LdGA dbdhH GdYGQajf s
(3BNQgG (B:s
(3hRGj aj BNQ GdMQa BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs